Answer:
b. average total cost = total cost/quantity of output
Step-by-step explanation:
The marginal cost is the additional cost of producing one more unit of output and it can be calculated by taking the change in total cost and dividing it by the change in quantity, its formula is:
- <em>Marginal cost = change in total cost/ change in quantity</em>
The average total cost (sometimes referred to simply as average cost) is total cost divided by the quantity of output, its formula is:
- <u><em>Average total cost = total cost / quantity of output</em></u>
The total cost is obtained adding together the fixed costs and the variable costs, its formula is:
- <em>Total cost = fixed cost + variable cost</em>
The average variable cost is obtained when variable cost is divided by quantity of output, its formula is:
- <em>Average variable = variable cost / quantity of output</em>
I hope you find this information useful and interesting! Good luck!
Answer:
D
Step-by-step explanation:
step 2 : x + 3 = 0 and x - 5 = 0 ← correct
step 3
x = 3 and x = - 5 ← error made here with signs, correct statement should be
x + 3 = 0 ⇒ x = - 3
x - 5 = 0 ⇒ x = 5
Answer:
<em>Factored Form: </em><em> </em><em>( y - 2 )( 3y + 7 )</em>
Step-by-step explanation:
<em>1. Let us first write down the problem at hand: </em>3y^2 + y - 14
<em>2. Now let us break this expression into groups: </em>
3y^2 - 6y + 7y - 14 ⇒ ( 3y^2 - 6y )( 7y - 14 )
<em>3. Factor 3y from 3y^2 - 6y:</em>
3y^2 - 6y ⇒ 3y( y - 2 )
<em>4. Factor 7 from 7y - 14:</em>
7y - 14 ⇒ 7( y - 2 )
<em>5. Substitute Step #3, 4 ⇒ Step #2:</em>
3y( y - 2 ) + 7( y - 2 )
<em>6. Factor common term y - 2:</em>
<em>Answer: ( y - 2 )( 3y + 7 )</em>
X=-8/15......................